The Effect of Basic Life Support Health Education to Improve Adolescent Knowledge Level - Tentrem, Wahyu Asal; Diyanah Syolihan Rinjani Putri (Gaster, 2024)
ABSTRACT Background: Cardiac arrest is the sudden loss of the heart's pumping function. According to American Heart Association (AHA) guidelines, approximately 350,000 adults in the United States experience a heart attack. The aim of this research is to determine the effect of basic health education on the level of knowledge of adolescents using video applications and simulation methods. Methods: This research is a quantitative research with a quasi-experimental research design before and after tests without control. The research sample was taken using a general sampling technique, namely. 40 respondents. The Wilcoxon test was used to analyze data to determine the effect of basic health education with video applications and simulation methods on the level of knowledge. Result: The pre-test results of providing basic health education through video applications and simulation methods were mostly in the poor category, namely not good. 24 respondents (60%). The increase in post test data points after initial training with video applications and simulation methods was good for 40 respondents (100%). The results of the Wilcoxon test analysis show a P value of (0.000). Conclusion: It can be concluded that there is an influence of basic life support health education with video applications and simulation methods on adolescent knowledge level